To solve the system of equations, we can substitute the value of x from the second equation into the first equation.
Substituting x = 5y - 1 into the first equation, we get:
2(5y - 1) + 6y = -18
10y - 2 + 6y = -18
16y - 2 = -18
Adding 2 to both sides, we have:
16y = -16
Dividing both sides by 16, we get:
y = -1
Now, substitute this value of y back into the second equation to find x:
x = 5(-1) - 1
x = -5 - 1
x = -6
So, the solution to the system of equations is (-6, -1).
Solve the system of equations. 2x+6y=−18 x=5y−1 (1 point) Responses (−6, −1) left parenthesis negative 6 comma negative 1 right parenthesis (5.25, 1.25) left parenthesis 5.25 comma 1.25 right parenthesis (−7.25, −1.25) left parenthesis negative 7.25 comma negative 1.25 right parenthesis (4, 1)
1 answer